2014
DOI: 10.1164/rccm.201307-1227oc
|View full text |Cite
|
Sign up to set email alerts
|

Attenuated Bordetella pertussis Vaccine Protects against Respiratory Syncytial Virus Disease via an IL-17–Dependent Mechanism

Abstract: Rationale: We attenuated virulent Bordetella pertussis by genetically eliminating or detoxifying three major toxins. This strain, named BPZE1, is being developed as a possible live nasal vaccine for the prevention of whooping cough. It is immunogenic and safe when given intranasally in adult volunteers.Objectives: Before testing in human infants, we wished to examine the potential effect of BPZE1 on a common pediatric infection (respiratory syncytial virus [RSV]) in a preclinical model.Methods: BPZE1 was admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 49 publications
1
37
0
Order By: Relevance
“…Laboratory data analysis highlighted a higher neutrophil count and higher C‐RP levels in infants with a single infection than in multiple infection. Although this finding has to our knowledge never been reported in humans, Schnoeller et al found similar results in neonatal mice in which a Bordetella pertussis respiratory infection seemed to protect against RSV‐induced disease in adult life, through a still incompletely understood mechanism involving interleukin‐17 and 10.…”
Section: Discussionsupporting
confidence: 53%
“…Laboratory data analysis highlighted a higher neutrophil count and higher C‐RP levels in infants with a single infection than in multiple infection. Although this finding has to our knowledge never been reported in humans, Schnoeller et al found similar results in neonatal mice in which a Bordetella pertussis respiratory infection seemed to protect against RSV‐induced disease in adult life, through a still incompletely understood mechanism involving interleukin‐17 and 10.…”
Section: Discussionsupporting
confidence: 53%
“…The use of an attenuated B. pertussis strain administered intranasally has been successfully tested in animal models and moved to Phase I clinical trials. 39,40 Although this is a promising application that has shown some advantages, 41,42 it shares the potential safety concerns related to the use of attenuated pathogens. 39 An interesting alternative that combines some of the above-mentioned strategies is the use of outer membrane vesicles, also called nanoparticles, which contain bacterial surface antigens.…”
Section: Development Of Improved Pertussis Vaccinementioning
confidence: 99%
“…In addition to provide full protection against pertussis challenge in mice, this vaccine also cross-protects against challenge with Bordetella parapertussis and Bordetella bronchiseptica [106]. In addition, it has interesting bystander effects, as it also protects against influenza virusinduced pneumonia [107] respiratory syncytial virus disease [108] and allergic asthma [109]. This live nasal vaccine has now undergone a human Phase I clinical trial and was found to induce immune responses in all colonized individuals without causing any vaccine-related adverse event [110].…”
Section: Pathogen Adaptation and Conclusionmentioning
confidence: 99%